CRYSTALLO-CO-AGGLOMERATION OF SIMVASTATIN: IMPROVING DISSOLUTION AND MICROMERITIC PROPERTIES - Indra Indra; Gustania Intan Indriani; Tuslinah Lilis (Pharmacoscript, 2024)
Simvastatin (SMV), a poorly soluble drug, faces challenges in pharmaceutical formulation due to its limited solubility and poor flow properties. This study aimed to enhance the physicochemical properties of SMV by preparing spherical crystals using a crystallo-co-agglomeration. Spherical crystals of SMV were prepared by dissolving the drug in methanol and adding it to an aqueous solution containing PVP K-30 and PEG 6000 under constant stirring. The resulting agglomerates were filtered, dried, and characterized using Fourier Transform Infrared (FTIR) spectroscopy, Powder X-Ray Diffraction (PXRD), Differential Scanning Calorimetry (DSC), Scanning Electron Microscopy (SEM), and dissolution testing. Micromeritic properties, including bulk density, Hausner ratio, compressibility index, angle of repose, and flowability, were also evaluated. FTIR confirmed the chemical integrity of SMV with minor shifts indicating interactions with stabilizers. PXRD and DSC analyses revealed reduced crystallinity and partial amorphization in the spherical crystals. SEM showed spherical morphology. Dissolution testing demonstrated a significantly enhanced dissolution rate for the spherical crystals compared to pure SMV. Improved micromeritic properties were also observed, indicating better flowability and packing density. Spherical crystallization significantly improved the solubility, dissolution rate, and flowability of SMV. This technique offers a promising strategy for enhancing the bioavailability and pharmaceutical performance of poorly soluble drugs.